2010
DOI: 10.1111/j.1365-2982.2010.01650.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of apneas in very preterm infants is increased after non-acid gastro-esophageal reflux

Abstract: Non-acid GER is responsible for a variable amount of AOP detected after-GER: this novel finding must be taken into consideration when a therapeutic strategy for this common problem is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 23 publications
(45 reference statements)
2
18
0
1
Order By: Relevance
“…We have previously shown [4] that apneas occur more frequently after than before GER episodes, and that non-acid GER, which is prevalent soon after feeding [6], is a more powerful trigger for apneas than acid GER [5]. We hypothesized that GERs occurring in the early postprandial period could easily evoke an apnea by a mechanism related to the mechanical distension of the mid-esophagus and independent from their acidity [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown [4] that apneas occur more frequently after than before GER episodes, and that non-acid GER, which is prevalent soon after feeding [6], is a more powerful trigger for apneas than acid GER [5]. We hypothesized that GERs occurring in the early postprandial period could easily evoke an apnea by a mechanism related to the mechanical distension of the mid-esophagus and independent from their acidity [5].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that GERs occurring in the early postprandial period could easily evoke an apnea by a mechanism related to the mechanical distension of the mid-esophagus and independent from their acidity [5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the severity of GER was not predictive of AOP. In a subsequent investigation, the authors found no significant difference in the duration or esophageal height of GER episodes associated with, versus without, apnea [10]. …”
mentioning
confidence: 99%